Teaching Design-A Thought for the Day - Singh, Ripudaman (Journal of Engineering Education Transformations, 1991)
Design - synthesis by definition and creative in- action, is a mould that shapes the future. With limited resources and ever growing needs, our standard of living tomorrow, largely depends upon how our design engineers are trained today. The uplift of the society comes from the practice of design as an art & science of systematically creating products or services to meet the needs. Thus the key to national progress lies in quality of design teaching.